Paradigma Manajemen Syari’ah - Zainil Ghulam (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2017)
The term of management actually being familiar because meaning of management practically is arrange everything properly, accurately and completely. Sharia management is not value-free management because the orientation of Sharia management is not only in earthly life but also the implications of ukhrawiyah. The terms of Sharia management is still debated as well as Sharia accounting, bank of Sharia, Sharia economic and so on. Sharia management is a management to obtain optimal results that ending in search of Allah's pleasure. Therefore it is all the steps taken in implementing the management should be based on the rules of Allah. The rules are contained in the Koran, Hadith and some examples and models has made by companions of the prophet Muhammmad SAW. Sharia management paradigm has three basics such as theology of shariah management, culture of shariah management, moral basis of shariah management. There are four foundations to develop management in the view of Islam, namely: truth, honesty, openness, and expertise. A manager should have four main properties that the exercise of management is to get maximum results. The most important thing in management is based on the Islamic view which should to be leadership. Leadership in Islam is a major factor in the concept of management. Management in the view of Islam is a fair management (‘adl).